2018
DOI: 10.1159/000495803
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Index (KIDMED) Adherence, Socioeconomic Determinants, and Nutritional Status of Portuguese Children: The Eat Mediterranean Program

Abstract: Background: Despite its health benefits, adherence to the Mediterranean diet (MD) has been decreasing, particularly in young generations and in Mediterranean regions, including Portugal. Socioeconomic and lifestyle factors have been shown to influence children and adolescents’ eating habits. This study aimed to assess the association between socioeconomic factors and children’s nutritional status with the MD adherence using the Eat Mediterranean (EM) program. Methods: Participant’s BMI and adherence to the MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…The data from the KIDMED questionnaire (low 41.6%, average 44.05%, and high adherence to the MD, 14.28%) provide notably lower results than those of studies conducted in Mediterranean countries [56,57], but similar to those of studies carried out in non-Mediterranean countries [19]. In turn, the results obtained in the current study match those found by similar studies in southern European countries [20,58,59], with a comparable percentage in subjects with a medium adherence to the MD, but with higher results in those who presented a low adherence to the MD. However, the adherence is inferior in comparison to the results of a recent study by Galan-Lopez et al, conducted in Icelandic adolescents, and where 14.99% of low adherence was found, 60.72% of mild adherence, and 24.29% of high adherence [24].…”
Section: Discussionsupporting
confidence: 56%
“…The data from the KIDMED questionnaire (low 41.6%, average 44.05%, and high adherence to the MD, 14.28%) provide notably lower results than those of studies conducted in Mediterranean countries [56,57], but similar to those of studies carried out in non-Mediterranean countries [19]. In turn, the results obtained in the current study match those found by similar studies in southern European countries [20,58,59], with a comparable percentage in subjects with a medium adherence to the MD, but with higher results in those who presented a low adherence to the MD. However, the adherence is inferior in comparison to the results of a recent study by Galan-Lopez et al, conducted in Icelandic adolescents, and where 14.99% of low adherence was found, 60.72% of mild adherence, and 24.29% of high adherence [24].…”
Section: Discussionsupporting
confidence: 56%
“…The daily consumption of a second piece of fruit, the variable with the highest differentiating power in our CHAID analysis, was reported by 37•8 % of our sample (n 123). This prevalence was lower than the one reported by Rito et al (47•9 %) for the same variable, in another recent study also developed in Portugal (57) .…”
Section: Discussioncontrasting
confidence: 63%
“…Similar results have been observed in other studies carried out with Spanish and Portuguese children. In Spain, the enKid study showed an optimal adherence in 46.4% of children [ 34 ], while The Eat Mediterranean Program in Portugal reported an optimal adherence in 58.4% of the sample [ 43 ]. These results are in contrast with other Mediterranean countries, such as Greece, Cyprus, or, to a lesser extent, Italy, where lower optimal MD adherence percentages have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Children’s age, gender, and school educational level, all of them previously related to the adherence to the MD in several studies [ 10 , 33 , 38 , 39 , 40 ], were recorded. Other variables related to adherence to the MD, such as parental educational level [ 41 , 42 , 43 ] and the school’s area and setting [ 30 , 38 , 40 ], were also recorded. The collection of these variables allows us to control them as possible confounding variables.…”
Section: Methodsmentioning
confidence: 99%